2005
DOI: 10.1016/j.ics.2005.06.021
|View full text |Cite
|
Sign up to set email alerts
|

Intercellular adhesion molecule 1-dependent activation of interleukin 8 expression in Candida albicans-infected human gingival epithelial cells

Abstract: Increased induction of interleukin 8 (IL-8) and intercellular adhesion molecule 1 (ICAM-1) by oral epithelial cells may play a role in the host defense mechanism in oropharyngeal candidiasis; however, little is known about the expression feature of these molecules on human gingival epithelial cells (HGECs) during Candida albicans infection. In this report we present evidence that neutralization with antibody against ICAM-1 inhibited both the adherence of C. albicans to HGECs and the Candida-induced production … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…5b). Previously, we reported the ICAM-1-dependent activation of IL-8 expression in C. albicans-infected HGECs (Egusa et al, 2005). We investigated the relationship between the ICAM-1-dependent and IL-1a-dependent IL-8 mRNA induction using neutralizing mAbs against ICAM-1 and IL-1a (Fig.…”
Section: Il-8 Production By Stimulation With Heat-killed C Albicans mentioning
confidence: 99%
See 4 more Smart Citations
“…5b). Previously, we reported the ICAM-1-dependent activation of IL-8 expression in C. albicans-infected HGECs (Egusa et al, 2005). We investigated the relationship between the ICAM-1-dependent and IL-1a-dependent IL-8 mRNA induction using neutralizing mAbs against ICAM-1 and IL-1a (Fig.…”
Section: Il-8 Production By Stimulation With Heat-killed C Albicans mentioning
confidence: 99%
“…Previously, we reported that HGECs induce IL-8 production in response to C. albicans infection via ICAM-1 signaling (Egusa et al, 2005). C. albicans expresses on the cell surface b2 integrin-like proteins that are involved in adhesion and morphogenesis (Hostetter, 1999); these C. albicans proteins may bind to ICAM-1 on HGECs as a ligand, resulting in the activation of IL-8 gene transcription (Egusa et al, 2005).…”
Section: Article In Pressmentioning
confidence: 99%
See 3 more Smart Citations